Preparation method of silicon carbide composite wave-absorbing material

By ultrasonicating the liquid metal of gallium indium alloy with silicon carbide powder, a composite silicon carbide absorbing material is formed, which solves the problem of difficult to regulate the dielectric characteristics of a single silicon carbide, and achieves efficient electromagnetic wave absorption and impedance matching.

CN119799280APending Publication Date: 2025-04-11ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510001860.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The dielectric properties of a single silicon carbide are difficult to regulate, resulting in impedance matching imbalance, limiting its application in the field of electromagnetic wave absorption.

Method used

The liquid metal of gallium indium alloy is prepared by mixing and heating with metal indium, and ultrasonic treatment is carried out with silicon carbide powder to form a silicon carbide composite wave absorbing material.

Benefits of technology

The absorption performance of silicon carbide composite wave absorbing materials is improved, and the effective absorption and impedance matching of electromagnetic waves is achieved, which is suitable for the preparation of high-performance electromagnetic wave absorbing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799280A_ABST
    Figure CN119799280A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a silicon carbide composite wave-absorbing material, and belongs to the technical field of inorganic composite wave-absorbing materials. The method comprises the following steps: mixing metal gallium and metal indium, and heating until the metal gallium and the metal indium are completely molten into liquid, so as to obtain gallium-indium alloy liquid metal; mixing the silicon carbide powder with a dispersing agent to obtain a uniform solution containing silicon carbide; the gallium-indium alloy liquid metal and the uniform solution containing silicon carbide are mixed and subjected to ultrasonic treatment, so that the gallium-indium alloy liquid metal is converted into powder to be compounded with the uniform solution containing silicon carbide, and a silicon carbide composite wave-absorbing material solution is obtained; and stirring the silicon carbide composite wave-absorbing material solution to obtain the target silicon carbide composite wave-absorbing material. The target silicon carbide composite wave-absorbing material prepared by the embodiment of the invention meets the following indexes: the thickness is lt; and the effective absorption bandwidth is adjustable in a range of 2GHz to 40GHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic composite absorbing materials, and in particular to a method for preparing a silicon carbide composite absorbing material. Background Art

[0002] With the rapid development of electronic science and technology, electronic devices such as computers and 5G communication base stations have become ubiquitous in human production and daily life. While these devices use electromagnetic waves as carriers of electronic information, they also radiate them, causing serious electromagnetic interference problems and posing a significant threat to human health and the normal operation of precision electronic equipment. Therefore, given the increasing popularity of GHz-band electromagnetic wave applications, the demand for high-performance new electromagnetic wave absorbing materials is becoming increasingly urgent. Such materials should not only provide excellent electromagnetic attenuation, but also possess outstanding environmental adaptability and low energy consumption. This is of great significance for improving the anti-interference performance of electronic equipment, reducing electromagnetic pollution, and protecting human health.

[0003] Silicon carbide, an inorganic material characterized by high temperature and corrosion resistance, high hardness, and excellent mechanical properties in extreme environments, primarily relies on dielectric loss to attenuate incident electromagnetic waves. However, this is limited by its low complex dielectric constant, poor conductivity loss, and poor magnetic loss. Consequently, the dielectric properties of a single silicon carbide are difficult to control, often leading to impedance matching imbalances and significantly limiting its application in electromagnetic wave absorption. Summary of the Invention

[0004] The present application provides a method for preparing a silicon carbide composite absorbing material to solve the following technical problem: how to improve the absorbing performance of the silicon carbide composite absorbing material.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing a silicon carbide composite absorbing material, the method comprising:

[0006] The metal gallium and the metal indium are mixed and heated until the metal gallium and the metal indium are completely melted into liquid.

[0007] GaIn alloy liquid metal is obtained;

[0008] mixing silicon carbide powder with a dispersant to obtain a uniform solution containing silicon carbide;

[0009] The gallium-indium alloy liquid metal is mixed with the uniform solution containing silicon carbide and ultrasonicated to convert the gallium-indium alloy liquid metal into powder, thereby obtaining a silicon carbide composite absorbing material solution.

[0010] Optionally, the weight ratio of the metal gallium to the metal indium is (1-8):1.

[0011] Optionally, the weight of the gallium-indium alloy liquid metal is 0.1% to 10% of the weight of the dispersant.

[0012] Optionally, the weight of the silicon carbide powder is 0.5% to 20% of the weight of the dispersant.

[0013] Optionally, the weight ratio of the silicon carbide powder, the gallium-indium alloy liquid metal and the dispersant is (0.4-4):(0.2-2):50.

[0014] Optionally, the ultrasonic process parameters include: ultrasonic power of 100W to 500W, and ultrasonic time of 20min to 40min.

[0015] Optionally, the heating process parameters include: temperature of 30°C to 200°C, and time of 30min to 60min.

[0016] Optionally, the dispersant includes at least one of the following: water and anhydrous ethanol.

[0017] Optionally, the mixing of the gallium-indium alloy liquid metal and the homogeneous solution containing silicon carbide and ultrasonic treatment to convert the gallium-indium alloy liquid metal into powder to obtain a silicon carbide composite absorbing material solution comprises:

[0018] Mixing the gallium-indium alloy liquid metal with the homogeneous solution containing silicon carbide and ultrasonically treating the mixture to convert the gallium-indium alloy liquid metal into powder, thereby obtaining a silicon carbide composite absorbing material solution;

[0019] The silicon carbide composite absorbing material solution is stirred to obtain the target silicon carbide composite absorbing material; wherein,

[0020] The stirring process parameters include: a stirring speed of 50 r / min to 500 r / min, and a stirring time of 30 min to 60 min.

[0021] Optionally, the target silicon carbide composite absorbing material meets the following indicators: thickness is less than 6 mm, and effective absorption bandwidth is adjustable from 2 GHz to 40 GHz.

[0022] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0023] The preparation method of the silicon carbide composite absorbing material provided in an embodiment of the present application includes: mixing metal gallium and metal indium and heating them until the metal gallium and the metal indium are completely melted into a liquid to obtain a gallium-indium alloy liquid metal; mixing silicon carbide powder with a dispersant to obtain a homogeneous solution containing silicon carbide; and mixing the gallium-indium alloy liquid metal with the homogeneous solution containing silicon carbide and ultrasonicating the mixture to convert the gallium-indium alloy liquid metal into a powder to obtain a silicon carbide composite absorbing material solution. Gallium metal has a low melting point and a high boiling point, while indium metal has good ductility and plasticity. Indium metal can interact with gallium metal, and the melting point of the gallium-indium alloy liquid metal can be regulated, thereby effectively compounding with silicon carbide to prepare an absorbing material with excellent wave-absorbing properties. Gallium metal and indium metal are mixed and heated to completely melt the gallium and indium metals into a liquid state, thereby regulating the uniformity, stability, and performance of the gallium-indium alloy liquid metal. Silicon carbide powder is mixed with a dispersant so that the silicon carbide powder is evenly dispersed in the dispersant, thereby obtaining a uniform solution containing silicon carbide. Ultrasonic mechanical vibration and cavitation effects can promote the compounding of the gallium-indium alloy liquid metal and silicon carbide. The energy released by the collapse of microbubbles generated by ultrasonic vibration is sufficient to break the surface tension of the gallium-indium alloy liquid metal, causing the gallium-indium alloy liquid metal to disperse and transform into a powder. The specific surface area of ​​the powdered gallium-indium alloy liquid metal is increased, providing more active sites, thereby enhancing the interaction with the silicon carbide powder and improving the wave-absorbing properties of the silicon carbide composite absorbing material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0026] Figure 1 A schematic flow chart of a method for preparing a silicon carbide composite absorbing material provided in an embodiment of the present application;

[0027] Figure 2 The X-ray diffraction spectrum of a silicon carbide composite absorbing material provided in Examples 1 to 3 of the present application;

[0028] Figure 3 The effective absorption bandwidth diagram of a silicon carbide composite absorbing material provided in Examples 1 to 3 of the present application (reflection loss value is less than -10dB);

[0029] Figure 4 A reflection loss diagram of a silicon carbide composite absorbing material provided in Example 1 of the present application;

[0030] Figure 5 A reflection loss diagram of a silicon carbide composite absorbing material provided in Example 2 of the present application;

[0031] Figure 6 This is a reflection loss diagram of a silicon carbide composite absorbing material provided in Example 3 of the present application. DETAILED DESCRIPTION

[0032] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0033] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a hard limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numbers within the range. For example, the description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0034] In this application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the terms "include", "comprise", etc. mean "including but not limited to". In this article, "at least one" refers to one or more, and "a plurality" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively. In the proportional relationships involved in this article, the parameters that need to be described by proportion should be understood as the first terms of the proportional formula in the order of description, and the proportional numbers should be understood as the second terms of the proportional formula. For example, if the mass ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond one-to-one to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0035] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0036] Silicon carbide (SiC) is a compound composed of silicon (Si) and carbon (C), with the chemical formula SiC. It is an inorganic non-metallic material with many excellent properties such as high hardness, high temperature resistance, and good chemical stability. Silicon carbide has excellent electromagnetic properties, good physical properties, and the advantages of strong designability. However, as an inorganic material with high temperature resistance, corrosion resistance, high hardness, and excellent mechanical properties in extreme environments, silicon carbide mainly relies on dielectric loss to attenuate incident electromagnetic waves. However, it is limited by its low complex dielectric constant, poor conductivity loss, and poor magnetic loss capacity. Therefore, the dielectric properties of single silicon carbide are difficult to control, often resulting in impedance matching imbalance and greatly limiting its application in the field of electromagnetic wave absorption. In the embodiment of the present application, the gallium-indium alloy has a low melting point and excellent electrical and thermal conductivity, as well as unique low volatility. These properties enable the gallium-indium alloy liquid metal to remain stable at high temperatures without reacting or volatilizing with other elements such as silicon, boron, and carbon. Therefore, silicon carbide and gallium-indium alloy liquid metal are composited to prepare a dielectrically tunable absorbing material.

[0037] In a first aspect, the present invention provides a method for preparing a silicon carbide composite absorbing material. Figure 1 This is a flow chart of a method for preparing a silicon carbide composite absorbing material provided in an embodiment of the present application; see Figure 1, the method comprising:

[0038] S1. Mixing metallic gallium and metallic indium and heating them until the metallic gallium and the metallic indium are completely melted into liquid to obtain a gallium-indium alloy liquid metal;

[0039] In some embodiments, the weight ratio of the metallic gallium to the metallic indium is (1-8):1.

[0040] Gallium metal has a low melting point (29.76°C) and a high boiling point (~1500°C), as well as excellent fluidity and electrical conductivity. Indium metal has good ductility and plasticity, making it useful in electromagnetic wave absorbing materials to increase the material's conductivity. Indium metal also interacts with gallium metal, allowing the melting point of the gallium-indium alloy liquid metal to be controlled, enabling it to be effectively combined with silicon carbide to produce an absorbent material with excellent absorbing properties. Gallium and indium metal are mixed and heated to completely melt the gallium and indium into a liquid state, allowing the compositional uniformity, stability, and properties of the gallium-indium alloy liquid metal to be controlled. Gallium-indium alloy liquid metal exhibits high electrical and thermal conductivity, low viscosity, and is non-toxic, making it suitable for use in the preparation of electromagnetic wave absorbing materials. The low melting point, low vapor pressure, high boiling point, high fluidity, and high ductility of gallium and indium metals are unique to other metals, which typically require high temperatures to achieve these properties. Room-temperature liquid metals, such as mercury, often have high vapor pressures, are highly toxic, and are prone to leakage. Therefore, gallium-indium alloy liquid metal is selected as the raw material of the absorbing material (electromagnetic wave absorbing material).

[0041] Based on the gallium-indium alloy phase diagram, mixing gallium and indium in different proportions can lower the melting point of the mixed metals, effectively producing room-temperature gallium-indium alloy liquid metal. Furthermore, the interaction between gallium and indium can produce a high-melting-point liquid metal, which can be effectively combined with silicon carbide to form a new high-temperature resistant electromagnetic wave absorption material. The weight ratio of gallium to indium can be (1-8):1, allowing the gallium-indium alloy liquid metal to remain liquid at room temperature while maintaining the properties of the gallium-indium alloy liquid metal under liquid conditions. If the weight ratio of metal gallium to metal indium is higher than 8:1, the melting point of the gallium-indium alloy liquid metal may increase, thereby affecting the stability of the gallium-indium alloy liquid metal under high temperature conditions. This is because when the weight ratio of metal gallium to metal indium is close to 3:1, a eutectic gallium-indium alloy is formed, which has the lowest melting point. If the weight ratio of metal gallium to metal indium is lower than 1:1, the electrical conductivity and thermal conductivity of the gallium-indium alloy liquid metal may decrease. The electrical conductivity and thermal conductivity of indium are lower than those of gallium, thereby affecting the electromagnetic wave absorption efficiency. At the same time, the excessive weight of indium increases the hardness of the gallium-indium alloy liquid metal, which is not conducive to the molding and processing of the gallium-indium alloy liquid metal. For example, the weight ratio of metal gallium to metal indium can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, etc.

[0042] In some embodiments, the heating process parameters include: temperature of 30° C. to 200° C., and time of 30 min to 60 min.

[0043] In the embodiment of the present application, the heating temperature and heating time are related to the proportion of metal indium. The greater the proportion of metal indium, the higher the heating temperature and the longer the required heating time. The heating temperature can be 30°C to 160°C, which can fully melt metal gallium and metal indium, accurately control the melting process of the gallium-indium alloy, and ensure the uniformity and stability of the composition of the gallium-indium alloy liquid metal. At the same time, the heating temperature range can be regulated based on the proportion of metal gallium in the gallium-indium alloy liquid metal. The higher the proportion of metal gallium, the lower the melting temperature, and the higher the proportion of metal gallium, the higher the melting temperature. If the heating temperature is higher than 160°C, the gallium metal may be more easily oxidized by air under high temperature conditions, resulting in reduced conductivity of the gallium-indium alloy liquid metal, and high temperature conditions are not easy to operate and are less safe. If the heating temperature is lower than 30°C, the gallium metal and metal indium may not be completely melted, thereby affecting the uniformity and stability of the gallium-indium alloy liquid metal. Illustratively, the heating temperature can be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.

[0044] The heating time can be 30 to 60 minutes, ensuring that the gallium and indium metals are completely melted to form a uniform alloy liquid, thereby providing the gallium-indium alloy liquid metal with better electrical and thermal conductivity. A moderate heating time can also prevent the metal from oxidizing. For example, the heating time can be 30 minutes, 33 minutes, 35 minutes, 38 minutes, 40 minutes, 43 minutes, 45 minutes, 48 ​​minutes, 50 minutes, 83 minutes, 55 minutes, 58 minutes, 60 minutes, etc.

[0045] S2, mixing silicon carbide powder with a dispersant to obtain a uniform solution containing silicon carbide;

[0046] In some embodiments, the weight of the gallium-indium alloy liquid metal is 0.1% to 10% of the weight of the dispersant.

[0047] In some embodiments, the weight of the silicon carbide powder is 0.5% to 20% of the weight of the dispersant.

[0048] In some embodiments, the weight ratio of the silicon carbide powder, the gallium-indium alloy liquid metal, and the dispersant is (0.4-4):(0.2-2):50.

[0049] In some embodiments, the dispersant comprises at least one of the following: water and anhydrous ethanol.

[0050] In an embodiment of the present application, the weight of the gallium-indium alloy liquid metal can be 0.1% to 10% of the weight of the dispersant, which can fully enable the gallium-indium alloy liquid metal to have good thermal conductivity and can also be well composited with silicon carbide powder to form a high-temperature resistant wave absorbing material. If the weight of the gallium-indium alloy liquid metal exceeds 10% of the weight of the dispersant, it may lead to excess gallium-indium alloy liquid metal and increase the cost of the gallium-indium alloy liquid metal. If the weight of the gallium-indium alloy liquid metal is less than 0.1% of the weight of the dispersant, it is difficult to exert the high volatility of the gallium-indium alloy liquid metal, and the characteristics of the high-temperature resistant wave absorbing material are not met. It is also difficult to rely on silicon carbide to effectively control the dielectric properties of the composite material to achieve effective absorption of electromagnetic waves. Exemplarily, the weight of the gallium-indium alloy liquid metal can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. of the weight of the dispersant.

[0051] The weight of the silicon carbide powder can range from 0.5% to 20% of the weight of the dispersant. The silicon carbide powder is dispersed in the dispersant to form a homogeneous silicon carbide solution. An appropriate amount of silicon carbide powder can significantly improve the hardness, strength, and wear resistance of the composite material. It can also enhance the thermal conductivity and heat resistance of the composite material, making it suitable for high-temperature environments. It can also effectively control the dielectric properties of the composite material and its electromagnetic wave absorption performance. If the weight of the silicon carbide powder is higher than 20% of the weight of the dispersant, the toughness of the composite material may be reduced, and the dielectric properties of silicon carbide may be difficult to control. As a low-dielectric material, excessive addition of silicon carbide will cause silicon carbide to play a dominant role in the absorbing material, making it difficult to improve the absorbing performance of silicon carbide, and thus difficult to achieve effective attenuation of electromagnetic waves and achieve effective absorbing effects. If the weight of the silicon carbide powder is lower than 0.5% of the weight of the dispersant, the gallium-indium alloy liquid metal may play a dominant role and have high conductivity, effectively reflecting electromagnetic waves, which is not conducive to the absorption of electromagnetic waves. In addition, it is difficult for silicon carbide to completely cover the gallium-indium liquid metal, causing the absorbing material as a whole to appear in a liquid state with high flowability, making it difficult to apply in actual scenarios. Illustratively, the weight of the silicon carbide powder can be 0.5%, 0.7%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 13%, 14%, 15%, 16%, 17%, 20%, etc., based on the weight of the dispersant.

[0052] The dispersant can ensure that the silicon carbide powder is fully dispersed and prevents aggregation, thereby obtaining a uniform solution containing silicon carbide. The above-mentioned dispersant can be one or both of water and anhydrous ethanol.

[0053] In some embodiments, the weight ratio of silicon carbide powder, gallium-indium alloy liquid metal, and dispersant is (0.4-4):(0.2-2):50. For example, the weight ratio of silicon carbide powder can be 0.4:0.2:50, 2:1:50, 3:1:50, 4:2:50, 2:0.8:50, 3:2:50, etc.

[0054] S3. Mixing the gallium-indium alloy liquid metal and the uniform solution containing silicon carbide and ultrasonicating the mixture to convert the gallium-indium alloy liquid metal into powder, thereby obtaining a silicon carbide composite absorbing material solution.

[0055] In some embodiments, the ultrasonic process parameters include: ultrasonic power of 100W to 500W, and ultrasonic time of 20min to 40min.

[0056] In the embodiments of the present application, the mechanical vibration and cavitation effect of ultrasound can promote the recombination of gallium-indium alloy liquid metal and a homogeneous solution containing silicon carbide. The energy released by the microbubbles generated by the ultrasonic vibration when they collapse is sufficient to break the surface tension of the gallium-indium alloy liquid metal, causing the gallium-indium alloy liquid metal to disperse and transform into a powder. The specific surface area of ​​the powdered gallium-indium alloy liquid metal increases, providing more active sites, thereby enhancing the interaction with the silicon carbide powder and improving the absorbing performance of the silicon carbide composite absorber. The metallic gallium in the gallium-indium alloy liquid metal has excellent fluidity and electrical conductivity. Under ultrasonic conditions, it will become micro-nano spheres based on the cavitation effect and mechanical vibration, thereby achieving effective electromagnetic wave attenuation and impedance matching. At the same time, both have good thermal conductivity and high temperature resistance, and can achieve effective electromagnetic wave absorption under high temperature conditions.

[0057] Ultrasonic power can be 100W to 500W, which can promote the effective composite dissolution of silicon carbide powder and gallium-indium alloy liquid metal. Ultrasonic power of 100W to 500W can generate sufficient cavitation effect and mechanical action, promoting the mixing and composite between silicon carbide powder and gallium-indium alloy liquid metal, increasing the reaction rate, and ultimately achieving in-situ growth of silicon carbide on the liquid metal. If the ultrasonic power is higher than 500W, the cavitation effect on the gallium-indium alloy liquid metal may be aggravated, and it may be completely broken up by the ultrasound, making it difficult to realize the high electrical conductivity, thermal conductivity, and high-temperature resistance of the gallium-indium alloy liquid metal. If the ultrasonic power is lower than 100W, the gallium-indium alloy liquid metal may be difficult to disperse, remaining in a liquid state and difficult to convert into powder, resulting in the performance of the obtained silicon carbide composite absorber material not meeting the standards. Illustratively, the ultrasonic power can be 100W, 130W, 150W, 180W, 200W, 230W, 250W, 280W, 300W, 330W, 350W, 380W, 400W, 430W, 450W, 480W, 500W, etc.

[0058] The ultrasonic treatment time can be 20 to 40 minutes, so that the gallium-indium alloy liquid metal microspheres generated under the ultrasonic action effectively react with the silicon carbide, so that the silicon carbide powder effectively covers the microspheres and prevents leakage of the gallium-indium alloy liquid metal. Exemplary ultrasonic treatment times can be 20 minutes, 23 minutes, 25 minutes, 28 minutes, 30 minutes, 33 minutes, 35 minutes, 38 minutes, 40 minutes, etc.

[0059] In some embodiments, the mixing of the gallium-indium alloy liquid metal and the homogeneous solution containing silicon carbide and ultrasonic treatment to convert the gallium-indium alloy liquid metal into powder to obtain a silicon carbide composite absorbing material solution comprises:

[0060] Mixing the gallium-indium alloy liquid metal with the homogeneous solution containing silicon carbide and ultrasonically treating the mixture to convert the gallium-indium alloy liquid metal into powder, thereby obtaining a silicon carbide composite absorbing material solution;

[0061] S4, stirring the silicon carbide composite absorbing material solution to obtain the target silicon carbide composite absorbing material; wherein,

[0062] The stirring process parameters include: a stirring speed of 50 r / min to 500 r / min, and a stirring time of 30 min to 60 min.

[0063] In an embodiment of the present application, the silicon carbide composite absorbing material solution is stirred at a stirring speed of 30 r / min to 200 r / min and a stirring time of 30 min to 60 min, thereby further promoting the complete compounding of the gallium-indium alloy liquid metal and silicon carbide in the silicon carbide composite absorbing material solution, thereby obtaining the target silicon carbide composite absorbing material with excellent absorbing performance. Exemplarily, the stirring speed can be 50r / min, 60r / min, 70r / min, 80r / min, 90r / min, 100r / min, 110r / min, 120r / min, 130r / min, 140r / min, 150r / min, 160r / min, 170r / min, 180r / min, 190r / min, 200r / min, 300r / min, 400r / min, 500r / min, etc.; the stirring time can be 30min, 35min, 40min, 45min, 50min, 55min, 60min, etc.

[0064] The silicon carbide composite absorbing material solution is stirred and then subjected to solid-liquid separation to obtain a solid substance; the solid substance is washed and dried in sequence to obtain the target silicon carbide composite absorbing material; wherein the drying temperature can be 50° C. to 100° C., and the drying time can be 2 hours to 12 hours.

[0065] In some embodiments, the target silicon carbide composite absorber material meets the following criteria: a thickness of less than 6 mm and an effective absorption bandwidth adjustable from 2 GHz to 40 GHz. For example, the effective absorption bandwidth of the S1 sample at a thickness of 2.60 mm is 2.60 GHz (frequency range 8.25-10.85 GHz); the effective absorption bandwidth of the S2 sample at a thickness of 2.40 mm is 4.40 GHz (frequency range 9.10-13.50 GHz); and the effective absorption bandwidth of the S3 sample at a thickness of 1.90 mm is 3.36 GHz (frequency range 8.40-11.76 GHz). Specifically, the effective absorption bandwidth represents the range within which the reflection loss value is less than -10 dB at a certain thickness. A reflection loss value less than -10 dB indicates that 90% of the electromagnetic wave energy at that frequency point is calculated to be absorbed.

[0066] The present invention provides a method for preparing a silicon carbide composite absorbing material, which has the following advantages:

[0067] 1. Mixing and heating metallic gallium and metallic indium is a key starting step in preparing gallium-indium alloy liquid metal. Metal gallium has the characteristics of a low melting point (about 29.8°C) and a high boiling point, which allows it to be transformed into a liquid at a relatively low temperature, while metallic indium has good ductility and plasticity, making it convenient for mixing operations. During the heating process, as the temperature rises, the two completely melt into liquids, thereby obtaining gallium-indium alloy liquid metal. Metal indium can interact with metal gallium, and this interaction plays an important role in regulating the melting point of gallium-indium alloy liquid metal. By changing the ratio of metal gallium and metal indium, the melting point of the alloy can be varied within a certain range to better adapt to the subsequent process requirements of compounding with silicon carbide. At the same time, in the process of mixing and heating to complete melting, the composition uniformity, stability and performance of the gallium-indium alloy liquid metal can be regulated. The uniform composition ensures that the properties of each part of the alloy are consistent when participating in the subsequent composite reaction, and the stability ensures that there will be no problems such as composition segregation in the subsequent process. The good performance lays the foundation for effective composite with silicon carbide, which in turn helps to prepare absorbing materials with excellent absorbing properties.

[0068] 2. Mixing the silicon carbide powder with a dispersant aims to evenly disperse the silicon carbide powder in the dispersant, thereby obtaining a homogeneous silicon carbide solution. Silicon carbide powder typically has a tendency to agglomerate due to interactions between its particles, such as van der Waals forces. The dispersant, however, adsorbs onto the surface of the silicon carbide powder particles, reducing the attractive forces between them and causing them to separate and become evenly distributed within the dispersant medium. This homogeneous silicon carbide solution creates excellent conditions for subsequent compounding with the gallium-indium alloy liquid metal. The uniform dispersion of the silicon carbide powder ensures full and uniform contact with the gallium-indium alloy liquid metal during the compounding process, avoiding localized uneven compounding and ultimately facilitating the preparation of a silicon carbide composite absorber with stable performance and excellent absorption properties.

[0069] 4. During the ultrasonic mixing of the gallium-indium alloy liquid metal and the homogeneous solution containing silicon carbide, the mechanical vibration and cavitation effect of ultrasound play a key role. Ultrasonic mechanical vibration can cause the substances in the solution to vibrate at high frequencies, promoting continuous collision and friction between the gallium-indium alloy liquid metal and silicon carbide, increasing the chance of their contact and thus promoting their recombination. The cavitation effect of ultrasound generates microbubbles in the solution under the action of ultrasonic vibration. These microbubbles rapidly collapse after growing to a certain size, releasing a huge amount of energy at the moment of collapse, which is sufficient to break the surface tension of the gallium-indium alloy liquid metal, causing it to disperse and transform into a powder.

[0070] 5. The significantly increased specific surface area of ​​the powdered gallium-indium alloy liquid metal means that each unit mass of alloy provides more active sites. These active sites can interact more strongly with atoms and functional groups on the surface of the silicon carbide powder, such as forming chemical bonds and electrostatic adsorption. This enhanced interaction optimizes the microstructure of the silicon carbide composite absorber, enabling more effective absorption and attenuation of electromagnetic waves propagating within the material, ultimately improving the absorbent performance of the silicon carbide composite absorber.

[0071] Overall, this preparation method ensures the effective preparation of silicon carbide composite absorbing materials and the improvement of their absorbing performance from multiple aspects by rationally utilizing the respective properties of metal gallium, metal indium and silicon carbide, combined with methods such as ultrasonic treatment, providing a feasible path for the research and development of high-performance absorbing materials.

[0072] The present application will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present application only and are not intended to limit the scope of the present application. The experimental methods in the following examples where specific conditions are not specified are usually measured in accordance with national standards. If there are no corresponding national standards, then the methods are carried out in accordance with general international standards, conventional conditions, or the conditions recommended by the manufacturer.

[0073] Example 1

[0074] A method for preparing a silicon carbide composite absorbing material, specifically comprising:

[0075] Step 1: Mixing metallic gallium and metallic indium and heating them to obtain gallium-indium alloy liquid metal;

[0076] Specifically, 8g of gallium and 1g of indium were accurately weighed and thoroughly mixed. The mixture was then placed on an electric heating table until the two metals were completely melted into a liquid state, with mechanical stirring continuously used during the process. The heating temperature of the electric heating table was 80°C and the heating time was 30 minutes.

[0077] Step 2: mixing silicon carbide powder with a dispersant to obtain a uniform solution containing silicon carbide;

[0078] Specifically, 0.4 g of silicon carbide powder was weighed and added to 50 g of deionized water, and the mixture was stirred thoroughly until the solution formed a homogeneous phase to obtain a homogeneous solution containing silicon carbide;

[0079] Step 3: mixing the gallium-indium alloy liquid metal and the uniform solution containing silicon carbide and ultrasonicating the mixture to convert the gallium-indium alloy liquid metal into a powder to obtain a silicon carbide composite absorbing material solution;

[0080] Specifically, 0.5 g of the prepared gallium-indium alloy liquid metal was weighed and added to the silicon carbide precursor prepared above, and the silicon carbide precursor / gallium-indium alloy liquid metal mixed solution was placed in an ultrasonic device, and the ultrasonic power was adjusted to 300 W and the ultrasonic time was adjusted to 20 minutes to obtain a silicon carbide composite absorbing material solution;

[0081] Step 4: Stirring the silicon carbide composite absorbing material solution and performing solid-liquid separation to obtain a solid substance; washing and drying the solid substance in sequence to obtain the target silicon carbide composite absorbing material.

[0082] Specifically, the silicon carbide composite absorbing material solution was placed on a magnetic stirring table and stirred continuously for 30 minutes at a stirring speed of 200 r / min; the silicon carbide composite absorbing material solution was stirred and then filtered, during which it was washed three times with anhydrous ethanol and deionized water, and then placed in a 60°C forced air drying oven for 2 hours.

[0083] Example 2

[0084] A method for preparing a silicon carbide composite absorbing material, specifically comprising:

[0085] Step 1: Mixing metallic gallium and metallic indium and heating them to obtain gallium-indium alloy liquid metal;

[0086] Specifically, 2g of gallium and 1g of indium were accurately weighed and thoroughly mixed. The mixture was then placed on an electric heating table until the two metals were completely melted into a liquid state, with mechanical stirring continuously used during the process. The heating temperature of the electric heating table was 160°C and the heating time was 40 minutes.

[0087] Step 2: mixing silicon carbide powder with a dispersant to obtain a uniform solution containing silicon carbide;

[0088] Specifically: weigh 2g of silicon carbide powder and add 50g of deionized water, stir thoroughly until the solution forms a homogeneous phase.

[0089] Obtaining a uniform solution containing silicon carbide;

[0090] Step 3: mixing the gallium-indium alloy liquid metal and the uniform solution containing silicon carbide and ultrasonicating the mixture to convert the gallium-indium alloy liquid metal into a powder to obtain a silicon carbide composite absorbing material solution;

[0091] Specifically, 1 g of the prepared gallium-indium alloy liquid metal was weighed and added to the silicon carbide precursor prepared above. The silicon carbide precursor / gallium-indium alloy liquid metal mixed solution was placed in an ultrasonic device. The ultrasonic power was adjusted to 500 W and the ultrasonic time was adjusted to 30 minutes to obtain a silicon carbide composite absorbing material solution.

[0092] Step 4: Stirring the silicon carbide composite absorbing material solution and performing solid-liquid separation to obtain a solid substance; washing and drying the solid substance in sequence to obtain the target silicon carbide composite absorbing material.

[0093] Specifically, the silicon carbide composite absorbing material solution was placed on a magnetic stirring table and stirred continuously for 30 minutes at a stirring speed of 100 r / min; the silicon carbide composite absorbing material solution was stirred and then filtered, washed three times with anhydrous ethanol and deionized water, and then placed in a 60°C forced air drying oven for 8 hours.

[0094] Example 3

[0095] A method for preparing a silicon carbide composite absorbing material, specifically comprising:

[0096] Step 1: Mixing metallic gallium and metallic indium and heating them to obtain gallium-indium alloy liquid metal;

[0097] Specifically, 1g of gallium and 1g of indium were accurately weighed and thoroughly mixed together. The mixture was then placed on an electric heating table until the two metals were completely melted into a liquid state. Mechanical stirring was continuously used during the process. The heating temperature of the electric heating table was 120°C and the heating time was 60 minutes.

[0098] Step 2: mixing silicon carbide powder with a dispersant to obtain a uniform solution containing silicon carbide;

[0099] Specifically: weigh 4g of silicon carbide powder and add 50g of deionized water, stir thoroughly until the solution forms a homogeneous phase.

[0100] Obtaining a uniform solution containing silicon carbide;

[0101] Step 3: mixing the gallium-indium alloy liquid metal and the uniform solution containing silicon carbide and ultrasonicating the mixture to convert the gallium-indium alloy liquid metal into a powder to obtain a silicon carbide composite absorbing material solution;

[0102] Specifically, 0.5 g of the prepared gallium-indium alloy liquid metal was weighed and added to the silicon carbide precursor prepared above, and the silicon carbide precursor / gallium-indium alloy liquid metal mixed solution was placed in an ultrasonic device, and the ultrasonic power was adjusted to 100 W and the ultrasonic time was 40 minutes to obtain a silicon carbide composite absorbing material solution;

[0103] Step 4: Stirring the silicon carbide composite absorbing material solution and performing solid-liquid separation to obtain a solid substance; washing and drying the solid substance in sequence to obtain the target silicon carbide composite absorbing material.

[0104] Specifically, the silicon carbide composite absorbing material solution was placed on a magnetic stirring table and stirred continuously for 30 minutes at a stirring speed of 500 r / min; the silicon carbide composite absorbing material solution was stirred and then filtered, during which it was washed three times with anhydrous ethanol and deionized water, and then placed in a 60°C forced air drying oven for 12 hours.

[0105] Figure 2 The X-ray diffraction spectrum of a silicon carbide composite absorbing material provided in Examples 1 to 3 of the present application is shown in FIG. Figure 2 (S1 is Example 1, S2 is Example 2, and S3 is Example 3); it shows that Examples 1 to 3 all successfully composited liquid metal and silicon carbide material (the crystalline diffraction peak of SiC and the amorphous diffraction peak of gallium-indium alloy liquid metal appeared).

[0106] Figure 3 This is a graph of the effective absorption bandwidth of a silicon carbide composite absorbing material provided in Examples 1 to 3 of the present application (reflection loss value is less than -10dB); please refer to Figure 3 , Figure 3It specifically shows the electromagnetic wave absorption characteristics of the composite material. Specifically, the horizontal axis represents the electromagnetic wave frequency range (2-18GHz) measured by the coaxial method, and the vertical axis represents different thicknesses. Therefore, each point in the figure represents the reflection loss value under different thicknesses on the vertical axis within the frequency range. The effective absorption bandwidth is clearly marked in the figure, marking the maximum effective absorption bandwidth of each sample and its corresponding thickness.

[0107] Figure 4 A reflection loss diagram of a silicon carbide composite absorbing material provided in Example 1 of the present application; Figure 5 A reflection loss diagram of a silicon carbide composite absorbing material provided in Example 2 of the present application; Figure 6 This is a reflection loss diagram of a silicon carbide composite absorbing material provided in Example 3 of this application. Figures 4 to 6 , Figures 4 to 6 Contains Figure 3 Where S1 is the three-dimensional graph of Example 1, S2 is the three-dimensional graph of Example 2, and S3 is the three-dimensional graph of Example 3. The projection of the reflection loss value is Figure 3 , Figures 4 to 6 Mark the minimum reflection loss value of the corresponding sample (-10dB means it can effectively absorb 90% of the energy of electromagnetic waves, -20dB means it can effectively absorb 99% of the energy of electromagnetic waves, -30dB means it can effectively absorb 99.9% of the energy of electromagnetic waves, and -40dB means it can effectively absorb 99.99% of the energy of electromagnetic waves).

[0108] Figure 3 (S1 is Example 1) and Figure 4 The figure shows the electromagnetic wave absorption performance of the liquid metal-assisted silicon carbide composite absorber S1 prepared in this example, measured using a vector network analyzer. Within the 2-18 GHz test range, the effective absorption bandwidth at a thickness of 2.50 mm, with an RL <-10 dB (90% absorption of electromagnetic waves), is 2.60 GHz (8.25-10.85 GHz), and the minimum reflection loss is -29.70 dB (RL <-20 dB attenuates 99% of electromagnetic waves), demonstrating effective absorption of electromagnetic waves in this band.

[0109] Figure 3 (S2 is Example 2) and Figure 5 The electromagnetic wave absorption performance of the liquid metal-assisted silicon carbide composite absorber S2 prepared in this example was measured using a vector network analyzer. Within the 2-18 GHz test range, the effective absorption bandwidth at a thickness of 2.40 mm, with an RL <-10 dB (90% absorption of electromagnetic waves), was 4.40 GHz (9.10-13.50 GHz), and the minimum reflection loss was -39.00 dB (RL <-30 dB attenuates 99.9% of electromagnetic waves), demonstrating effective absorption of electromagnetic waves in this band.

[0110] Figure 3 (S3 is Example 3) and Figure 6 The electromagnetic wave absorption performance of the liquid metal-assisted silicon carbide composite absorber S3 prepared in this example was measured using a vector network analyzer. Within the 2-18 GHz test range, the effective absorption bandwidth at a thickness of 1.90 mm, with an RL <-10 dB (90% absorption of electromagnetic waves), was 3.36 GHz (8.40-11.76 GHz). The minimum reflection loss was -29.90 dB (RL <-30 dB attenuates 99% of electromagnetic waves), effectively absorbing 80% of X-band electromagnetic waves (8.20-12.40 GHz).

[0111] Comparative Example 1

[0112] Based on the disclosure of Example 1, the difference between Comparative Example 1 and Example 1 is that the amount of silicon carbide added is 5 g.

[0113] Results: Within the 2-18 GHz test range, the effective absorption bandwidth with RL < -10 dB (90% absorption of electromagnetic waves) at a thickness of 3.20 mm was 1.63 GHz (12.93-14.56 GHz), and the minimum reflection loss value was -34.70 dB (RL < -30 dB can attenuate 99.9% of electromagnetic waves), demonstrating effective absorption of electromagnetic waves within this band. Therefore, excessive addition of silicon carbide leads to a decrease in the dielectric constant, which manifests as a weakening of the absorption performance. The effective absorption bandwidth decreases from 2.60 GHz to 1.63 GHz with an increase in thickness from 2.50 mm to 3.20 mm. This is due to the low dielectric constant of silicon carbide. Excessive silicon carbide content leads to an increase in the proportion of silicon carbide, resulting in a decrease in overall electromagnetic parameters and a weakening of the absorption performance.

[0114] Comparative Example 2

[0115] Based on the disclosure of Example 1, Comparative Example 2 differs from Example 1 in that the amount of gallium-indium alloy liquid metal added is 5 g.

[0116] Results: Within the 2-18 GHz test range, the minimum return loss was -6.62 dB, failing to reach -10 dB, significantly reducing electromagnetic wave absorption performance. Therefore, excessive addition of gallium-indium alloy liquid metal leads to a significant decrease in electromagnetic wave absorption performance. This is because the surface of the gallium-indium alloy liquid metal forms dense gallium oxide, an insulating material that hinders electron transmission and makes it difficult to effectively attenuate incident electromagnetic waves. Therefore, regulating the gallium-indium alloy liquid metal content is crucial in the examples of this application.

[0117] The target silicon carbide composite absorbing materials of Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to high temperature resistance tests.

[0118] Under high temperature conditions, since silicon carbide and gallium-indium alloy liquid metal are both high-temperature resistant materials, and the two composite materials will not react further under high temperature conditions, the dielectric constant of the material tends to show a decreasing trend under high temperature conditions, resulting in a certain decrease in the material's wave absorbing performance. Therefore, the two high-temperature resistant materials are compounded and can be used as high-temperature resistant materials, and can have certain high-temperature wave absorbing properties. The wave absorbing performance test was carried out at 500°C in the range of 12.4-18GHz, among which Examples 1 to 3 can achieve more than 60% absorption of electromagnetic waves, which is better than conventional high-temperature resistant wave absorbing materials. The absorption rates of Comparative Examples 1 to 2 are all less than 40%. Please see Table 1 for specific results:

[0119] Table 1 High temperature resistance test results of target silicon carbide composite absorbing materials

[0120] High temperature absorption performance Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 X-band absorptivity 64% 71% 66% 31% 24%

[0121] One or more technical solutions in the embodiments of the present application may have at least the following technical effects or advantages:

[0122] (1) The method for preparing the silicon carbide composite absorbing material of the embodiment of the present application is simple to operate, has low dependence on preparation equipment, and is easy to be produced on an industrial scale;

[0123] (2) In the embodiment of the present application, liquid gallium-indium metal and silicon carbide powder are ultrasonically treated to prepare powder, which can transform the liquid metal from liquid to powder, thereby better meeting practical applications;

[0124] (3) The silicon carbide composite absorbing material prepared in the embodiment of the present application has the characteristics of thin thickness, strong attenuation ability, good and adjustable absorbing performance, and has good application prospects in the field of absorbing materials.

[0125] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.

Claims

1. A method for preparing a silicon carbide composite absorbing material, the method comprising: Mixing metal gallium and metal indium and heating them until the metal gallium and the metal indium are completely melted into liquid to obtain gallium-indium alloy liquid metal; mixing silicon carbide powder with a dispersant to obtain a uniform solution containing silicon carbide; The gallium-indium alloy liquid metal is mixed with the uniform solution containing silicon carbide and ultrasonically treated to transform the gallium-indium alloy liquid metal into powder, thereby obtaining a silicon carbide composite wave absorbing material solution.

2. The method according to claim 1, characterized in that The weight ratio of the metal gallium to the metal indium is (1-8):

1.

3. The method according to claim 1, characterized in that The weight of the gallium-indium alloy liquid metal is 0.1% to 10% of the weight of the dispersant.

4. The method according to claim 1, characterized in that: The weight of the silicon carbide powder is 0.5% to 20% of the weight of the dispersant.

5. The method according to claim 1, 4 or 5, characterized in that: The weight ratio of the silicon carbide powder, the gallium-indium alloy liquid metal and the dispersant is (0.4-4):(0.2-2):

50.

6. The method according to claim 1, characterized in that The ultrasonic process parameters include: ultrasonic power of 100W to 500W, and ultrasonic time of 20min to 40min.

7. The method according to claim 1, characterized in that The heating process parameters include: temperature of 30° C. to 200° C. and time of 30 min to 60 min.

8. The method according to claim 1, characterized in that The dispersant includes at least one of the following: water and anhydrous ethanol.

9. The method according to claim 1, characterized in that: The step of mixing the gallium-indium alloy liquid metal with the uniform solution containing silicon carbide and ultrasonically treating the mixture so as to convert the gallium-indium alloy liquid metal into powder to obtain a silicon carbide composite absorbing material solution comprises: The gallium-indium alloy liquid metal is mixed with the uniform solution containing silicon carbide and subjected to ultrasonic treatment to convert the gallium-indium alloy liquid metal into powder to obtain a silicon carbide composite absorbing material solution; The silicon carbide composite absorbing material solution is stirred to obtain the target silicon carbide composite absorbing material; wherein, The stirring process parameters include: a stirring speed of 50 r / min to 500 r / min, and a stirring time of 30 min to 60 min.

10. The method according to claim 9, characterized in that The target silicon carbide composite absorbing material meets the following indicators: thickness is less than 6 mm, and effective absorption bandwidth is adjustable from 2 GHz to 40 GHz.